On what is true: return to Althusser, detour via Lacan - Viedma, Celeste (ARFIL y UNL, 2022)
This article aims to retake the concepts of problematic and epistemological rupture presented by Althusser in various articles of Marx’s Theoretical Revolution, which it seeks to relate to Lacan’s considerations in Seminar IX about the Cartesian cogito. In discussion with some of the contemporary readings of both authors, it seeks to account for a certain affinity in their proposals regarding the possibility of an encounter with reality and the proposal of what is true other than the guarantee of Truth. Finally, it presents the Althusserian conceptualization of theoretical practice as a work process that links Generalities and the conception of an ethics of practice (theoretical, analytical, political) given by the possibility of giving an account of oneself.